Kinerja Dinas Kesehatan Kota Padang dalam Melakukan Pengawasan terhadap Kualitas Air Minum Isi Ulang di Kecamatan Kuranji - Liola Defitri; Zikri Alhadi (Al-DYAS, 2026)
The quality of refill drinking water is an important aspect of public health protection because consuming water that does not meet established standards can increase the risk of health problems. Although a regulatory framework for supervision is available, the implementation of supervision over Refill Drinking Water Depots (DAMIU) must be evaluated to ensure compliance with hygiene, sanitation, and drinking water quality requirements. This study aims to analyze the performance of the Padang City Health Office in supervising the quality of refill drinking water in Kuranji Subdistrict and identify the factors influencing the implementation of such supervision. The study employed a qualitative approach with a descriptive design. Data were collected through in-depth interviews, observations, and document analysis and were subsequently analyzed based on Dwiyanto’s five indicators of public organization performance: productivity, service quality, responsiveness, responsibility, and accountability. The findings indicate that supervision over DAMIU has been implemented with the support of regulations, Regional Health Laboratory (Labkesda) facilities, a network of community health centers, and environmental sanitation personnel; however, its implementation remains suboptimal. The productivity and equitable distribution of supervision are constrained by limited human resources and the extensive range of facilities requiring supervision, while service quality is restricted by the suboptimal implementation of periodic testing. Responsiveness remains predominantly reactive, while regulatory and institutional support has not fully ensured the effectiveness of supervisory responsibility. Public accountability also remains suboptimal because information regarding the compliance status of DAMIU and supervision findings has not been fully disclosed. Other inhibiting factors include budgetary constraints, low compliance among some DAMIU owners, and limited public access to information. This study concludes that supervisory performance requires strengthened human resource capacity, periodic testing, business operator compliance, and public information disclosure. These findings imply the need for more systematic, equitable, responsive, and accountable supervision to ensure the safety of refill drinking water for the public.